Advanced distillation technologies : design, control, and applications - Kiss, Anton Alexandru (Chichester : John Wiley & Sons, 2013)
'Covers the background, recent developments, fundamental principles, design and simulation, detailed cases of separations in DWC, and future trends'--
Includes index.
Keywords: Distillation